A NEW ERIOPHYID MITE (ACARI: PROSTIGMATA) FROM INDIA - JOSHI, SUSHILA; MENON, PRATIBHA; V. V. RAMAMURTHY (The Bioscan, 2013)
A new species of eriophyid (Acari: Prostigmata) viz. Aceria amrini n. sp., was collected from Tamarix aphylla (Tamaraceae), from India. The distinguishing characters are 6 rayed empodium, prodorsal shield clear with no lines or granules, dorsal annuli without microtubercles, microtubercles present only on the last few annuli ventrally, antapical seta and accessory seta present. The paper includes a key to Aceria spp. reported from Tamarix spp. and a checklist of all eriophyid species known on Tamarix spp. with details on their synonyms, type host, damage symptoms and type locality.